Can mothers rely on the Brazilian health system for their deliveries? An assessment of use of the public system and out-of-pocket expenditure in the 2004 Pelotas Birth Cohort Study, Brazil - Barros, Aluísio JD (BioMed Central, 2008)
BACKGROUND: In a country where comprehensive free health care is provided via a public health system (SUS), an unexpected high frequency of catastrophic out-of-pocket expenditure has been described. We studied how deliveries were financed among mothers of a birth cohort and whether they were an important source of household out-of-pocket expenditure. METHODS: All deliveries occurring in the city of Pelotas, Brazil, during 2004, were recruited for a birth cohort study. All mothers were interviewed just after birth and three months later. Comprehensive data on the pregnancy, delivery, birth conditions and newborn health were collected, along with detailed information on expenses related to the delivery. RESULTS: The majority of the deliveries (81%) were financed by the public health system, a proportion that increased to more than 95% among the 40% poorest mothers. Less than 1% of these mothers reported some out-of-pocket expenditure. Even among those mothers covered by a private health plan, nearly 50% of births were financed by the SUS. Among the 20% richest, a third of the deliveries were paid by the SUS, 50% by private health plans and 17% by direct payment. CONCLUSION: The public health system offered services in quantity and quality enough to attract even beneficiaries of private health plans and spared mothers from the poorest strata of the population of practically any expense.